The development and evaluation of virtual reality environment for learning deoxyribonucleic acid (DNA) processes - Alvinson Roland, ak Roland Demong. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This paper presents the development process of Interactive DNA which is a virtual reality (VR) based learning tool for learning Deoxyribonucleic acid (DNA) processes that occur inside a cell. DNA process that was highlighted in this learning tool is basic gene expression which involves two processes, namely transcription and translation. The main purpose of this learning tool is to assist learners to learn about these processes in a constructive way. Learners can interact actively with the virtual molecule inside the virtual learning environment to construct their knowledge and understanding of the process. Software tools that were used in developing the learning tool are 3D Studio Max, Internet Scene Assembler and Macromedia Dreamweaver. The interface of the learning tool had also been evaluated iteratively based on the cooperative evaluation (CE) technique to ensure its usability.